Leasing in emerging markets - Carter, Laurence W.; Kuczynski, Irving; Barger, Teresa; International Finance Corporation; World Bank. (Washington, D.C. : World Bank, 1996)
The book writes on the experiences of IFC closely involved in promoting and advising the government of the developing countries on leasing and leasing regulations.
At head of title: International Finance Corporation.
"Prepared by Laurence Carter, Teresa Barger, and Irving Kuczynski"--5th prelim. p.
Includes bibliographical references: p. 63.
uaj 07/06/2013
Loans
Keywords: International Finance Corporation; Lease and rental services; Industrial promotion